Enzymatic Transformation and Bonding of Sulfonamide Antibiotics to Model Humic Substances - J. Schwarz; H. Knicker; G. E. Schaumann; S. Thiele-Bruhn (Journal of Chemistry)
Sulfonamides are consumed as pharmaceutical antibiotics and reach agricultural soils with excreta used as fertilizer. Subsequently, nonextractable residues rapidly form in soil, which has been researched in a couple of studies. To further elucidate conditions, strength, and mechanisms of the fixation to soil humic substances, three selected sulfonamides were investigated using the biochemical oligomerization of substituted phenols as a model for the humification process. Catechol, guaiacol, and vanillin were enzymatically reacted using laccase from Trametes versicolor. In the presence of the substituted phenols alone, the concentration of sulfonamides decreased. This decrease was even more pronounced when additional laccase was present. Upon the enzymatic oligomerization of the substituted phenols to a humic-like structure the sulfonamides were sorbed, transformed, sequestered, and nonextractable bound. Sulfonamides were transformed depending on their molecular properties. Fractions of different bonding strength were determined using a sequential extraction procedure. Isolated nonextractable products were analyzed by chromatographic, spectroscopic, and calorimetric methods to identify coupling and bonding mechanisms of the sulfonamides. Differential scanning calorimetry measurements suggested cross-linking of such incorporated sulfonamides in humic oligomers. Nuclear magnetic resonance spectroscopy measurements showed clear differences between the vanillin-sulfapyridine oligomer and the parent sulfapyridine indicating bound residue formation through covalent binding.